Financial Literature Sharia Accounting at Amil Zakat Institution - Yohanes C. Seralurin; Rudiawie Larasati; Victor Pattiasina (Universitas Serang Raya, 2023)
The Amil Zakat Institution As Salaam of Papua Province is a non-structural institution capable of organising activities for collecting and utilising Zakat, Infaq, and Shadaqah in a strong and credible organisational manner. However, Amil Zakat Institution is currently experiencing limitations in its financial reporting, which is presented per PSAK 109 concerning Zakat Financial Reporting. For this reason, this financial literacy service plays a role in helping and increasing financial literacy skills based on accounting standards and laws and regulations. This financial literacy service is carried out by training on preparing financial reports according to PSAK 109 and having the service team prepare simple financial applications using the help of a modified Excel application and then providing ongoing assistance. The training was carried out for five months. The result is that the trainees can take part in the activities properly and 70% of the trainees can practice the material presented regarding the application and make financial reports according to PSAK 109 using simple financial applications independently.